Контрaстивнaя лингвистикa и обучение инострaнным языкaм (Вестник КазНУ. Серия Востоковедения, 2017)
In non-native language teaching, the methods of applied contrastive linguistics are used to a certain extent, through proper and skillful use of these methods the methodology of teaching foreign languages can be improved significantly. The methods of contrastive linguistics are also used in the preparation of curriculum and training materials to teach foreign languages to adults, as their cognitive abilities and acquired knowledge of their native or second language serve as a support base for the formation of new language skills. In this process, the application of contrastive linguistics methods should take into account not only the age characteristics of the students, but other important factors such as - the goal for learning a foreign language, psychological conditions, motivation etc.This article sets out the views on the role of contrastive linguistics in teaching foreign languages; it also reviews the comparative method, as one of the main methods of contrastive linguistics.